Radiochemical Studies on the Separation of Cesium, Cobalt, and Europium from Aqueous Solutions Using Zirconium Selenomolybdate Sorbent - H. El-Said (Journal of Chemistry)
A procedure for removal and separation of Cs, Eu and activation product of Co using zirconium selenomolybdate was developed. Interactions of 134Cs(I), 152,154Eu(III), and 60Co(II) ions from HNO3 acid solutions with zirconium selenomolybdate matrix, dried at 50°C, have been individually investigated by the batch equilibration method. The sorption behavior of the three ions showed a selectivity sequence in the following order: Cs(I) > Eu(III) > Co(II). The breakthrough capacities of zirconium selenomolybdate for Cs(I), Eu(III) and Co(II) were found to be 0.82, 0.45, and 0.18 mmol/g of the sorbent, respectively. A mixture of the three radionuclides (1×10−2 M each) in 140 mL of 1×10−2 M HNO3 solution was passed through 1 g zirconium selenomolybdate chromatographic column. Thereafter, quantitative elution of the retained Co(II) was achieved with 14 mL of 1×10−1 M HNO3 acid solution leaving Eu(III) and Cs(I) strongly retained onto the column. Quantitative elution of Eu(III) was achieved by passing 22 mL 2.5×10−1 M HNO3. About 89% of the retained Cs(I) was eluted with 32 mL of 2 M NH4Cl solution at a flow rate of 0.5 mL/min.